Association between age and neurological outcomes in out-of-hospital cardiac arrest patients resuscitated with extracorporeal cardiopulmonary resuscitation: a nationwide multicentre observational study. Issue 1 (21st April 2021) - Miyamoto, Yuki; Matsuyama, Tasuku; Goto, Tadahiro; Ohbe, Hiroyuki; Kitamura, Tetsuhisa; Yasunaga, Hideo; Ohta, Bon
Abstract: Aims: Little is known about the difference in outcomes between young and old patients who received extracorporeal cardiopulmonary resuscitation (ECPR) for out-of-hospital cardiac arrest (OHCA). Therefore, we aimed to investigate the differences in outcomes between those aged ≥75 years and <75 years who experienced OHCA and were resuscitated with ECPR. Methods and results: We performed a secondary analysis of a nationwide prospective cohort study using the Japanese Association for Acute Medicine OHCA registry. We identified patients aged ≥18 years with OHCA who received ECPR. The patients were classified into three age groups (18–59 years, 60–74 years, and ≥75 years). The primary outcome was a 1-month neurological outcome. To examine the association between age and 1-month neurological outcome, we performed logistic regression analyses fitted with generalized estimating equations. From 2014 to 2017, we identified 875 OHCA patients aged ≥18 years who received ECPR. The proportion of patients who survived with favourable neurological outcome in the patients aged 18–59 years, 60–74 years, and ≥75 years were 15% (64/434), 8.9% (29/326), and 1.7% (2/115), respectively. In the multivariable analysis, compared with the age of 18–59 years, the proportions of favourable neurological outcomes were significantly lower in patients aged 60–74 years [adjusted odds ratio (OR), 0.44; 95% confidence interval (CI), 0.32–0.61] and those aged ≥75 years (adjusted OR, 0.26; 95% CI, 0.11–0.59). Conclusion: Advanced age (age ≥75 years in particular) was significantly associated with poor neurological outcomes in patients with OHCA who received ECPR. Graphical abstract: